Joint Security and Dependability Modeling: An Updated Overview - Thilina Pathirana; Ruxandra F. Olimid; Gianfranco Nencioni (IEEE Access)
The increasing demand for mission-critical services and applications has emphasized the need for systems with strict security and dependability requirements. In this context, evaluating and addressing the complex interplay between security threats and dependability challenges is essential. Joint modeling of security and dependability allows an early evaluation of such interplay and is essential to identify the weakness of a system before the actual deployment. This paper aims to provide an updated overview of joint security and dependability modeling. First, we present the foundational concepts of security and dependability. Then, we introduce the primary modeling techniques in detail. This background knowledge is used to categorize the state-of-the-art work on joint modeling based on three key dimensions: considered attacks and faults, modeled attributes, and used modeling techniques. This paper also illustrates how the joint modeling is applicable and fruitful in a system that enables mission-critical applications, such as the fifth generation (5G) of mobile networks and the Multi-access Edge Computing (MEC). Moreover, it individually presents the state-of-the-art security and dependability modeling of 5G-MEC systems. Finally, the paper discusses the opportunities and challenges of advanced approaches to joint models for the next generation of mission-critical services and applications.